Pharmacoepidemiology and pharmacovigilance in pregnancy: experience of the regional service of clinical pharmacology - E V Eliseeva; Yu V Feoktistova; E A Poddubnyi; I I Shmykova; R K Goncharova (IP Berlin A.V., 2013)
One of the priority healthcare tasks is the prevention of congenital malformations at all stages - pregravidal, prenatal and postnatal. The analysis of 1306 pregnant women' pharmacotherapy was carried out. 27,93% of the prescribed drugs were relatively safe for the fetus (category A, B). The most commonly used (36,12%) drugs were the ones with undetermined safety level (N FDA- Food and Drug Administration). In 35,93% of cases drugs with the risk of teratogenicity or embryotoxicity effects to the fetus (category C, D, X) were used.